Spontaneous cervical artery dissection: is it really a connective tissue disease? A comprehensive review - Gunduz, Muhammed Enes; Kadirvel, Ramanathan; Kallmes, David F.; Pezzini, Alessandro; Keser, Zafer (Frontiers in Neurology, 2023)
Background: Spontaneous cervical artery dissection(sCeAD) is an important cause of stroke in young adults. The underlying pathophysiology remains unclear, without validated biomarkers to identify subjects at risk. Previous studies suggested the role of abnormalities in the connective component of the arterial wall. Purpose: To assess dermal ultrastructural aberrations of connective tissue by skin biopsy and genetic variations in sCeAD patients. Method: We searched the PubMed and Scopus databases until August 2023 with PRISMA guidelines. Original articles assessing skin biopsy in sCeAD patients were included. Two reviewers independently conducted the screening. Findings: We included 16 studies compromising 459 patients. Thirteen studies assessed ultrastructural changes and found aberrations of collagen and elastic fibers, described as irregular contours and calibers of collagen fibrils, composite flower-like fibrils, fragmented moth-eaten elastin, and microcalcifications, cumulatively in 50.5% of patients. Seven studies showed no causative mutations in collagen type I,III,V, or elastin genes. One study showed linkage between connective tissue alterations and mutation on chromosomes 15q2 and 10q26 using genome-wide linkage analysis, while another study found significant copy number variant enrichments in genes involved in extracellular matrix (COL5A2/COL3A1/SNTA1) and collagen fibril organizations (COL5A2/COL3A1). Finally, differential expression of extracellular proteins was linked to connective tissue disorder in patients with recurrent sCeAD using a quantitative proteomics approach. Conclusion: Current literature supports the hypothesis that an underlying, subclinical connective tissue disorder, likely genetically determined, may predispose to arterial wall weakness and sCeAD. Further studies with larger sample sizes and robust methodology are needed to better define the role of connective tissue in sCeAD pathogenesis.